Rheumatic Diseases in China - Zeng, Qing Yu (BioMed Central, 2008)
INTRODUCTION: Epidemiological studies of rheumatic diseases have been conducted during the past 20 years in China. The aim of this study was to clarify prevalence rates of common rheumatic diseases in China. METHODS: Relevant reports of population-based surveys conducted from 1980 to 2006 were retrieved. Studies using the World Health Organization-International League of Associations for Rheumatology COPCORD (Community Oriented Program for Control of Rheumatic Diseases) protocol and those that did not employ this protocol but were published in recognized journals were identified and analyzed. RESULTS: Thirty-eight surveys including 241,169 adults from 25 provinces/cities were pooled for analysis. The prevalence of rheumatic complaints ranged from 11.6% to 46.4%, varying by locality, study protocol and age of the people surveyed. Prevalence of symptomatic osteoarthritis (OA) varied from 5.1% to 20.8%, with common sites of involvement being the lumbar spine, knee joint and cervical spine. Compared with rates of radiographic and symptomatic knee OA in the USA, elderly men in Beijing exhibited similar prevalence rates and elderly women exhibited a higher prevalence. The prevalence of hip OA and hand OA was much lower in Chinese than in Caucasian populations, but both kinds of OA were more common in coal miners. The prevalence of ankylosing spondylitis ranged from 0.2% to 0.54% among Han ethnic Chinese and were lower among mixed ethnic populations. The prevalence of psoriatic arthritis ranged from 0.01% to 0.1%, and that of reactive arthritis was 0.02%; undifferentiated spondyloarthropathy was identified in 0.64% to 1.2% of the individuals included in the surveys. The prevalence of rheumatoid arthritis (RA) ranged from 0.2% to 0.93%, with the highest rate being reported from a Taiwan urban area. In mainland China there were no significant differences in prevalence of RA between the northern and southern parts of China, or between different ethnic groups. The prevalence of hyperuricemia increased after the 1980s. The prevalence of gout was found to have increased in recent decades from 0.15% to 1.98%, apart from in the Taiwan aborigines, among whom the highest prevalence rate of 11.7% was recorded. The prevalence of primary Sjögren's syndrome in Beijing was 0.77% by the Copenhagen criteria and 0.33% by the San Diego criteria. The prevalence of soft tissue rheumatism was 2.5% to 5.7%. Fibromyalgia was seldom observed in China. CONCLUSION: Rheumatic diseases are common in China. The prevalence of rheumatic complaints varied with the locality surveyed. The prevalence of OA is comparable with that in Western countries but varies in terms of joint involvement. The prevalence of ankylosing spondylitis is similar to that in Caucasians. Except in Taiwan, the prevalence of RA in China is lower than that in developed countries. The prevalence of hyperuricemia and gout increased after the 1980s, but it remains lower than that in developed countries. More studies are required to evaluate prevalence rates among minority groups in the west and northwest parts of China, and further study is needed to address fibromyalgia in China.